METODE TAMYIZ DALAM KETERAMPILAN BAHASA ARAB SANTRIWAN (STUDI KASUS DI PONDOK PESANTREN MUQIMUSSUNNAH PALEMBANG) - Yanuar Arafat; Muhammad Misdar; Muhammad Naufal (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2020)
This research was aimed to obtain information regarding tamyiz method in students' Arabic language skills, internal and external problems of tamyiz method in students' Arabic language skills, and teacher problematic factors of tamyiz method in Muqimussunnah Islamic boarding schools. To achieve this goal, the qualitative approach is the method used in this research. Besides that, the descriptive method is also used to find out how the problematics of Arabic learning by using tamyiz method. In this study, researchers chose techniques and data collection tools that are relevant to the purpose of the study in this case researchers used interview techniques (interviews), observations, and documentation After conducting the research, the conclusions drew from it are: 1) Student problems are divided into two, namely internal and external problems. For internal problems, they are: attitudes toward learning, motivation to learn, and concentration of learning; 2) The teacher's problems, in this case, are divided into internal and external problems. For internal factors, the teacher's problems consist of: The teacher as the student's coach in learning, Management in learning, and classroom management. For external factors, teacher problems consist of Continuous self-development, learning facilities and infrastructure, assessment policies, student environment in schools, and curriculum in schools